Helminth parasites of amphibians: Two species of parasitic nematodes from Bufo spinulosus Trifolium (Tschudi) - Naupay, Asucena (1974)
In the present work on helminths parasites of Bufo spinulosus Trifolium (Tschudi) from Huanuco, we found two species, one of they is a new report to Peru.